The Effect of Short Story Poster on Young Learners’ Vocabulary Achievement in 5th Grade Students at SDN 1 Satera - Wiastra, I Gede Gita; LUH PUTU SINTA LEONY CAHYADEWI; I WAYAN MAWA; NI PUTU AYU KARTIKA SARI DEWI; NI PUTU WULANTARI (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2025)
This study investigates the effectiveness of using short story posters to enhance vocabulary achievement among young learners. Conducted at SD Negeri 1 Satera, the research involved 15 fifth-grade students during the 2024/2025 academic year. A classroom action research design was employed, with pretest and posttest data collected to measure the impact of the intervention. The results reveal a significant improvement in students' vocabulary achievement, with the average score increasing from 55.2 in the pretest to 78.6 in the posttest. The standard deviation decreased from 8.4 to 7.2, indicating more consistent performance across the group. The combination of narrative context and visual aids in short story posters proved effective in making vocabulary learning engaging and meaningful, catering to young learners' developmental needs and learning preferences.